Black Subversion: Historical and Contemporary Perspectives on the Black Diaspora in Germany (KULT_online, 2019)
The bilingual anthology The Black Diaspora and Germany / Deutschland und die Schwarze Diaspora provides insights into the experiences of the Black Diaspora in Germany as well as links to the international Black Diaspora. Contributions in the form of essays and interviews come from scientists, activists, and cultural professionals as well as contemporary witnesses. Historical perspectives and experiences of the Black Diaspora are complemented by contemporary ones. Topics of the anthology include historical overviews as well as reports of individual experiences, forms of Black activism in Germany, the connection between racism and nation, the position of Black people in cultural production, and the need for gendering the Black Diaspora.